The Role of International Organizations in Managing Global Health Security: A Study of World Health Organization Activities in Africa - Joseph Onovughe Siloko; Vincent Eseoghene Efebeh; Esekumenu V. Clark (Pinisi Journal of Social Science, 2025)
The study examines the role of international organizations, specifically the World Health Organization (WHO), in managing global health security in Africa. It evaluates WHO’s effectiveness, the impact of systemic inequality in resource allocation, and the consequences of delays in decision-making and operational inefficiencies. The research is anchored in regime theory, which explains how international organizations govern global health security through established norms and cooperative frameworks (Krasner, 1983). A qualitative research design was employed, utilizing data from WHO reports, global health indices, and case studies of past health crises, such as Ebola (2014–2016) and COVID-19 (2020–2024). Data were collected from WHO publications, African CDC reports, peer-reviewed journals, and government health statistics.  Findings reveal that WHO plays a pivotal role in disease surveillance, emergency response coordination, and health policy implementation. However, systemic inequalities in funding and material distribution have limited Africa’s ability to respond effectively to health crises. Delays in WHO’s decision-making processes have further exacerbated the impact of pandemics on the continent. Despite these challenges, WHO remains a key institution for strengthening health security, provided that operational inefficiencies are addressed, resource distribution becomes more equitable, and decision-making processes are restructured. The study recommends decentralizing WHO’s regional offices in Africa, improving health equity in resource allocation, and reducing bureaucratic inefficiencies to enhance rapid emergency response. These findings contribute to ongoing policy discussions on global health governance and sustainable health security strategies for Africa.